Canine Parvoviral Enteritis in a Five Month Old Golden Retriever - Wulandari, Chitra Dwi; Widyastuti, Sri Kayati; I Gede Soma (Journal of Applied Veterinary Science And Technology, 2025)
Background: Canine parvovirus (CPV) is a major cause of severe illness in dogs, particularly in unvaccinated puppies. The virus spreads rapidly and often leads to acute gastrointestinal disease with high morbidity and mortality. Purpose:  This case report describes the diagnosis and management of canine parvoviral enteritis in a young dog that presented with early clinical signs of infection. Case(s): A five-month-old female Golden Retriever named Golden, weighing 7.65 kg and light brown in color, was presented with a two-day history of anorexia, repeated vomiting (approximately five times per day), and bloody diarrhea. On physical examination, the patient was moderately dehydrated, with pale mucous membranes, delayed capillary refill time (>2 seconds), reduced skin turgor, and elevated heart and respiratory rates. Fecal examination revealed no intestinal parasites. Hematological analysis showed normocytic normochromic anemia, lymphocytosis, neutropenia, and thrombocytopenia. A rapid CPV antigen test confirmed the diagnosis of parvoviral infection. Based on the clinical and laboratory findings, the dog was diagnosed with canine parvoviral enteritis. Case Management: Treatment focused on supportive and symptomatic care. Cefotaxime (20 mg/kg body weight) was administered intravenously twice daily for five days to prevent secondary bacterial infection. To control vomiting, metoclopramide HCl (0.5 mg/kg body weight) was given intravenously. Supportive therapy included intravenous fluids (lactated Ringer’s solution) and vitamin B-complex supplementation. Conclusion:  The patient showed marked clinical improvement, including normalization of vital parameters, restoration of appetite and activity, and cessation of vomiting and diarrhea. The dog was considered clinically recovered at the end of the treatment period.